The Role of Communication in Building Early Childhood Social Skills at RA Arrahmah - Zubaedah, Annisa; Sianturi, Risbon; Nabila, Nazwa; Resviani, Resi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Communication is important in building children's social skills. Early childhood must have good social skills. Educators need to pay attention to aspects of children's language and social development, because without good communication, children will have difficulty socializing. This study is motivated by the importance of communication in building children's social skills, so that children can grow well and optimally. In this study, the approach used is descriptive qualitative, which aims to explore and understand the role of communication in developing the social skills of early childhood at RA Arrahmah. One of the main findings from the interview was that communication skills have become an integral part of all learning domains at RA Arrahmah. With the implementation of the 2024-2025 curriculum, teachers at RA Arrahmah have made changes in the form of using the independent curriculum. So all learning is integrated, including communication skills